Software for preliminary LTE network valuation - Одарченко, Р. С. (Problems of Informatization and Control, 2015)
This paper analyzes the main problems of the modern cellular networks in Ukraine, includingnetworks LTE. It is shown that the launch of this type of networks is an inevitable step in thedevelopment of information infrastructure of Ukraine, and therefore now require a special tool toestimate the value of networks LTE, which will enable mobile operators to conduct a preliminaryanalysis of the economic efficiency of the implementation of LTE networks. In this paper, the resultsdemonstrated the development of software describing basic functionality